Defoliation frequency affects morphophysiological traits in the bunchgrass Poa ligularis = La frecuencia de defoliación afecta las carcacterísticas morfofisiológicas en la gramínea perenne Poa ligularis - Gittins Lopez, Cecilia Gabriela (2010)
Poa ligularis is an important forage in Patagonian rangelands. Populations of this perennial bunchgrass have been severely affected by overgrazing. We propose that increased defoliation frequencies will decrease (1) aerial- and belowground dry matter production, (2) root survival, and (3) concentration and content of total non-structural crown + root carbohydrates, and (4) increase root mortality. Five defoliation frequencies (plus 1 control) were applied in a representative grassland of the Occidental District in Patagonia during two consecutive growing seasons. All four hypotheses were rejected. Aerial and belowground dry matter production increased from one to two or three defoliations. Root production and dynamics were not affected by the study defoliation frequencies. Total nonstructural carbohydrate (TNC) concentration (%) and content (g/ plant) in crown + roots were increased when defoliations augmented from three to five times (%, 2002-2003), or from two to three times (% and g/plant, 2003-04) during the growing cycle, but TNC contents in 2002-03. These results suggest that TNC availability in crown and roots, and plant vigor on P. ligularis in dry Patagonia are favored by light to moderate defoliation frequencies (no more than two or three defoliations annually) immediately before internode elongation to 5 cm stubble height each.